Children and death in the Bronze and early Iron Age Aegean - Gallou, Chrysanthi (Routledge, 2018)
The study of children and childhood remains largely marginalised in the archaeology of the prehistoric Aegean. Thus, this study aims to make Mycenaean children visible in archaeological research by discussing the treatment of non-adults at death in mainland Greece during the Bronze and Early Iron Age, with focus placed on grave types, grave furnishings, funerary and post-funerary rites and commemoration, and by highlighting the response of local communities to the death of their unfortunate little members, through the documentation of chronological and regional variations in a long perspective.